PENGARUH BIAYA PRODUKSI TERHADAP LABA BERSIH PERUSAHAAN DENGAN VOLUME PENJUALAN SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN TEKSTIL DAN GARMENT YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2019 - Ammy, Baihaqi (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
Textile and garment companies that show that the company's condition has decreased in net profit, but production costs and sales volume have increased, on the other hand, where the company's net profit has increased followed by an increase in production costs and sales volume. The purpose of this study is to determine the effect of production costs. on net income with sales volume as a moderating variable listed on the IDX for the 2016-2019 period.  This research uses associative and quantitative types. This study uses secondary data collection techniques in the form of corporate financial reports for the 2016-2019 period. The population in this study were 21 companies and the samples in this study were 14 companies. The data analysis technique used descriptive statistical testing, multiple linear regression, classical assumption test, hypothesis test, moderation regression analysis, and determination coefficient test. The results of this study indicate that production costs have a positive and significant effect on company net income and sales volume shows a negative and significant effect on company net income. In addition, it is also known that sales volume does not moderate the effect of production costs on company net income.